2005
DOI: 10.1007/bf02867403
|View full text |Cite
|
Sign up to set email alerts
|

Role of bilirubin, vitamin C and ceruloplasmin as antioxidants in coronary artery disease [CAD]

Abstract: A study has been carried out on 250 CAD patients to see how the serum levels of three antioxidants i.e., Vitamin C, Bilirubin and Ceruloplasmin are related to the CAD risk factors and characteristics in these patients. The number of severe category CAD patients declined by 7-18% with increasing serum levels of the three antioxidants and, triple vessel disease declined by 14-20%. A decline of 39% in Myocardial Infarction (MI) occurred with increasing serum Ceruloplasmin. Serum Ceruloplasmin was significantly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
2
7
0
2
Order By: Relevance
“…The findings of the present study are similar to those of the study conducted by Dubois Rande et al 30) and Mc Murray 31) which reported a significant rise in MDA level and lipid peroxidation, with a concomitant decrease in antioxidants in patients with unstable angina and chronic heart failure. The present study also concurs with studies of Verma et al,32) who demonstrated that there was a significant drop in antioxidant, whereas lipid peroxides were significantly higher in AMI patients, compared with controls. The findings of the present study are also in good agreement with those of the study conducted by Kharb 33) where significantly decreased levels of antioxidants and increased levels of lipid peroxides were reported.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the present study are similar to those of the study conducted by Dubois Rande et al 30) and Mc Murray 31) which reported a significant rise in MDA level and lipid peroxidation, with a concomitant decrease in antioxidants in patients with unstable angina and chronic heart failure. The present study also concurs with studies of Verma et al,32) who demonstrated that there was a significant drop in antioxidant, whereas lipid peroxides were significantly higher in AMI patients, compared with controls. The findings of the present study are also in good agreement with those of the study conducted by Kharb 33) where significantly decreased levels of antioxidants and increased levels of lipid peroxides were reported.…”
Section: Discussionsupporting
confidence: 93%
“…[25] The possible causes behind low vitamin C maybe due to over consumption as antioxidants, over used in regeneration of vitamin E also may be due to low dietary intake. Vitamin C had negatively correlated with the severity of the disease as shown in (Table-6) this result was agreed with other reports, [19,26] this meaningful result revealed that as vitamin C become low the oxidative stress become worse and the disease become more severe.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, a decrease of 14–20% was objectified in triple vessel disease and of 39% in MI with increasing serum CP in CHD patients, compared to the non-MI group. An inverse relationship was found between the three antioxidants studied and coronary risk factor suggesting that greater care in traditional risk factors would maintain a high level of these antioxidants [ 20 ].…”
Section: Resultsmentioning
confidence: 99%